Bromley Girls - Mendelsohn, Martha (Book collections on Project MUSE., 2015)
After Emily Winter, fourteen, makes a promising start at a posh, academically-challenging Manhattan girls' school in 1955, things turn sour but she discovers a knack for leadership as she copes with her best friend Phoebe's snubs, a newborn brother, snobbish classmates, and more.